A Quad-Helix Collaboration in Anticipating the Future-Oriented Skills for Business English Professionals - ANAS, Ismail (Research and Innovation in Applied Linguistics, 2025)
This review paper explores the role of quad-helix collaboration—comprising government, industry, academia, and media practitioners—in anticipating the future-oriented skills required by business English professionals. As the global business landscape continues to evolve, the demand for new skills in communication, digital literacy, cross-cultural competence, and data-driven decision-making is increasing. This paper examines how each sector within the quad-helix model contributes to identifying and fostering these skills. Government bodies provide policy frameworks and funding for skill development, while industries highlight the practical needs of the workforce. Academia is instrumental in research and curriculum design, and media practitioners reflect societal demands and trends that influence professional competencies. By synthesizing insights from these four sectors, the paper identifies emerging trends in Business English education and professional practice. The review emphasizes the need for a collaborative approach to skill development, proposing that a well-integrated quad-helix framework can effectively prepare business English professionals for future challenges. Additionally, it discusses the implications for curriculum design, professional development, and collaborative educational models, providing recommendations for stakeholders to bridge the gap between current training and future requirements. The paper concludes by suggesting future research directions to further explore the intersection of business English, skill development, and intersectoral collaboration.